The Treatment Algorithm for Meibomyitis, Hordeolum and Halazion - V. N. Trubilin; E. G. Poluninа; D. V. Andzhelova; Yu. V. Evstigneeva; K. V. Chinenova; V. Kumar; M. D. Pozharitsky (Oftalʹmologiâ)
Despite the fact that the frequency of treatment the eyelids inflammatory diseases affecting the modified sebaceous glands (Meibomian glands, Zeiss glands) is very high in outpatient clinical practice, and the basic principles of treating this pathology are well known to everyone, there are always many questions. Therefore, interdisciplinary approach with gastroenterologists, dermatologists,  endocrinologists and other specialists is often required treatment of this patients group. In addition, the transition of the inflammatory process to a chronic form and the encapsulation of the inflammatory focus and / or the formation of a halazion requires an accurate algorithm of actions from the practitioner, which depends on the duration of the pathological process. There is always a question — what form of an antibacterial drug is better to prescribe — ointment or drops? In addition, there is no consensus on the use of hormone therapy in the treatment of meibomyitis, hordeolum and chalazion. This article presents an algorithm for the prevention and treatment of this group of patients, which involves a certain sequence of therapeutic and preventive measures, depending on the severity and duration of the inflammatory process. Eyelid hygiene (warm compresses + self-massage of the eyelids with gel) is recommended in case of chronic blepharitis clinical signs, complaints of dryness, discomfort, wearing contact lenses. In case of the acute inflammatory process — meibomyitis and/or hordeolum in addition to eyelid hygiene, local antibiotic therapy is recommended. If a halazion is forming the choice of treatment tactics (local instillation therapy, intracapsular administration of a prolonged corticosteroid or surgical treatment) depends on the halazion duration (more or less than 2 months). The presented algorithm has the practical importance, since adequate treatment will not only eliminate the focus of chronic infection on the eyelids, but also improve the patient’s quality of life, since the presence of such a disease gives pronounced psycho-emotional discomfort because of its localization zone.